The Impact of a Transition of Care Program on Acute Myocardial Infarction Readmission Rates. (September 2018) - Marbach, Jeffrey A.; Johnson, Drew; Kloo, Juergen; Vira, Amit; Keith, Scott; Kraft, Walter K.; Margules, Natalie; Whellan, David
Hospital discharge is a high-risk time period, and acute myocardial infarction (AMI) patients often have early readmissions. The authors hypothesized that a multifaceted AMI care coordination program would reduce early hospital readmission rates. The outcomes of patients receiving care coordination (n = 304) were compared to patients receiving standard care (n = 192). Multivariable analyses of the outcomes were conducted by conditional logistic regression of propensity score matched sets. The primary outcome—hospital readmission within 30 days of discharge—occurred in 18% of standard care patients and 11.8% of care coordination patients. Patients receiving care coordination demonstrated a 48% reduction in odds of readmission within 30 days (odds ratio = 0.52; P = .04; 95% CI = 0.28-0.97). These results are the first to demonstrate that inclusion in an AMI-specific care coordination program is associated with a significantly lower risk of 30-day hospital readmission.